GHÉP ACRYLONITRIL LÊN CHITIN BẰNG KĨ THUẬT BỨC XẠ ĐỂ HẤP PHỤ KIM LOẠI NẶNG ĐỘC (As(V), Cd 2+) - Hạnh, Trương Thị; Hiến, Nguyễn Quốc; Huy, Hà Thúc (Vietnam Journal of Science and Technology, 2012)
GRAFING ACRYLONITRIL ONTO CHITIN BY PRE-IRRADIATION METHOD FOR ADSORPTION OF TOXIC HEAVY METAL IONS (As(V), Cd2+) Chitin with low deacetylation degree was obtained by partial deacetylation of chitin. Grafting for incorporation as well as modification of functional groups onto chitin prepared hybrid adsorbents aiming enhancement for adsorption of metal ions was carried out by irradiation technology. In this research, acrylonitril was used to graft onto chitin by pre-irradiation method. The maximal value of grafting degree was found to be 114% at acrylonitril concentration of 40% and the absorbed dose of 25 kGy. The conversion of the cyano group to amidoxime group with reactive agent of hydroxylamine in NaOH at 80oC may attain up 2.13 mmol/g for 6 hours. The As (V) and Cd2+ adsorption equilibrium onto AN-g-chitin-A fits with the Langmuir isotherm better than the Freundlich one. The adsorption capacities were determined to be 0.88 and 2.09 mg/g for As and Cd respectively. From removing Arsenic and Cadmium in groundwater sample, the chitin-g-AN-A has proved to be a promising material for cleanup of contaminated water by toxic metal ions.